Przygotowanie do nauki języka włoskiego jako rzadko używanego na poziomie uniwersyteckim: przedstawienie treści kulturowych i interkulturowych na Zintegrowanej Platformie Edukacyjnej - Kowalik, Katarzyna; Woch, Agnieszka (Neofilolog, 2025)
The aim of this paper is to reflect on the situation of teaching Italian as a less widely learned and taught language both in Poland and in the European context. It presents the difficulties arising from this situation and suggests way to teach the language in a broad cultural and intercultural context. Interactive e-materials developed for a ministerial project are referred to, resulting in the publication of a set of 400 e-learning units for teaching Italian, as a source of practical examples of the method we have adopted. This method can be used to better prepare future students for studying Italian.